The influence of nursing service quality on JKN patient satisfaction in class III inpatient rooms at RSUD Yogyakarta city - Emanuel Depa Chrisnandy; Muhammad Syamsyu Hidayat; Rochana Ruliyandari (Jurnal EduHealth, 2024)
The quality of nursing services is a very important component for hospitals which is one form of result of the level of patient satisfaction which can have an impact on the hospital's image. The aim of this research is to determine the influence of the quality of nursing services on national health insurance patient satisfaction in the inpatient ward of RSUD Yogyakarta City. This research used a cross-sectional approach with a total sample of 170 inpatient respondents. Research analysis used univariate, bivariate using the Chi-Square test and multivariate analysis using the multiple logistic regression test. The results of the univariate analysis were obtained for the dimensions of responsiveness, assurance and physical evidence, respondents rated them as not good, while for the dimensions of empathy and reliability, respondents rated them as very good. For the bivariate test, a significant relationship was found (p value < 0.05) between patient satisfaction and the dimensions of responsiveness, assurance, physical evidence, empathy and reliability. The results of the multivariate analysis showed that the dimensions most closely related to patient satisfaction were responsiveness, empathy and reliability. This research proves that there is an influence between the quality of nursing services and patient satisfaction. It is hoped that hospitals can improve and carry out continuous evaluations so that satisfaction is always well maintained.